"So my grandfather's two tours meant nothing?": Students struggle with the weight and responsibility of war. Issue 3 (16th August 2022) - Gibbs, Brian
Abstract: This manuscript describes the implementation of a co-created (teacher and researcher) unit of instruction focused on the teaching of war. This unit examines war through a critical lens and emphasizes anti-war movements. A design study this research investigated how the teaching of war as difficult knowledge can impact student sense of critical civic literacy and civic agency. Focused by two essential questions—What is a just war and how do we end war?—the unit of instruction presented in this study is a constant deliberation driven by inquiry and discussion. Findings indicate that student sense of critical civic literacy grew, with students gaining a more complex understanding of the history of the United States at war. There was also evidence that students gained insight into how to use their agency but felt overwhelmed and under practiced to create change in reality. Students recommended that this type of instruction be done earlier and more often in their schooling.